Electrode catalyst layer, membrane electrode assembly, and polymer electrolyte fuel cell
Patent Information
- Application Number
- JP2021071276
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-04-20
AI Technical Summary
【0015】 本発明によれば、高加湿条件及び低加湿条件の両方の運転条件における発電性能を向上させることができる。
Smart Images

Figure 0007643159000002 
Figure 0007643159000003 
Figure 0007643159000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode catalyst layer, a membrane electrode assembly, and a polymer electrolyte fuel cell. [Background technology]
[0002] As a measure to combat the ever-increasing burden on the global environment, there is a growing demand for cleaner energy sources. Fuel cells are power generation systems that generate electrical energy through a chemical reaction between hydrogen and oxygen, emitting only water, and there are high hopes for fuel cells as a future energy source.
[0003] Fuel cells are classified into alkaline, phosphoric acid, solid polymer, molten carbonate, and solid oxide types depending on the type of electrolyte. Solid polymer fuel cells can be used at around room temperature, so they are expected to be used widely as vehicle power sources and stationary home power sources. For this reason, research and development is being actively conducted to improve power generation characteristics and durability, reduce costs, and so on, in order to commercialize solid polymer fuel cells.
[0004] A solid polymer electrolyte fuel cell comprises a polymer electrolyte membrane having proton conductivity, a fuel electrode which is an anode, and an air electrode which is a cathode. The fuel electrode and the air electrode sandwich the polymer electrolyte membrane in the thickness direction of the polymer electrolyte membrane. The fuel electrode has an electrode catalyst layer which separates a fuel gas into protons and electrons. The air electrode has an electrode catalyst layer which oxidizes the protons transported through the polymer electrolyte membrane with an oxidizing agent containing oxygen, and receives electrons from an external circuit. The electrode catalyst layers of the fuel electrode and the air electrode contain a catalytic material such as a platinum-based precious metal, a carrier which supports the catalytic material, and a polymer electrolyte.
[0005] A polymer electrolyte fuel cell is made up of a plurality of stacked single cells, each of which has a basic structure in which a gas diffusion layer and a separator are arranged on the surface of the electrode catalyst layer of the fuel electrode and the air electrode opposite the polymer electrolyte membrane. The gas diffusion layer is a conductive layer for uniformly diffusing the reactant gas. The separator is a member that has a gas flow path and a cooling water flow path and plays a role in extracting electrons to an external circuit, and is arranged on the outside of the gas diffusion layer. Hereinafter, a unit in which a fuel electrode and an air electrode are formed on both sides of a polymer electrolyte membrane is referred to as a membrane electrode assembly.
[0006] In a polymer electrolyte fuel cell, a fuel gas containing hydrogen is supplied to the fuel electrode and an oxidant gas containing oxygen is supplied to the air electrode, whereby electrode reactions shown in the following formulas 1 and 2 occur at the fuel electrode and the air electrode, generating electricity.
[0007] Fuel electrode: H2→2H + +2e - ...(Formula 1) Air electrode: 1 / 2O2+2H + +2e - →H2O...(Formula 2) As shown in formula 1, fuel gas supplied to the anode is separated into protons and electrons by the catalytic material contained in the electrode catalyst layer of the anode. The separated protons move to the air electrode through the humidified polymer electrolyte and polymer electrolyte membrane contained in the electrode catalyst layer of the anode. The separated electrons are extracted from the anode to an external circuit, and move to the air electrode through the external circuit. As shown in formula 2, at the air electrode, the oxidant gas reacts with the protons and electrons that have moved from the anode to produce water. An electric current is generated when the electrons pass through the external circuit.
[0008] In order to increase the proton conductivity in the membrane electrode assembly, it is necessary to humidify the inside of the membrane electrode assembly to a relatively high level. For this reason, a humidifier is used to supplement the moisture in the system. However, from the viewpoint of reducing costs, which is an obstacle to the widespread use of fuel cells, it is desirable to eliminate the need for humidifiers. In order to eliminate the need for humidifiers, a membrane electrode assembly is required that can generate electricity under low humidification conditions without using a humidifier.
[0009] Known techniques relating to such membrane electrode assemblies are disclosed in Patent Documents 1 and 2. Patent Document 1 discloses a technique for improving power generation performance under low humidification conditions by providing a predetermined water retention layer and a hydrophobic moisture management layer between an electrode catalyst layer and a gas diffusion layer. Patent Document 2 discloses a technique for improving power generation performance under low humidification conditions by subjecting a constituent material of the gas diffusion layer to a hydrophilic treatment. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2019-169315 A [Patent Document 2] JP 2004-031325 A Summary of the Invention [Problem to be solved by the invention]
[0011] Conventional fuel cells using the electrode catalyst layers disclosed in Patent Documents 1 and 2 have room for improvement in terms of improving power generation performance under both high and low humidification operating conditions. [Means for solving the problem]
[0012] The electrode catalyst layer for solving the above problem is an electrode catalyst layer joined to a polymer electrolyte membrane in a membrane electrode assembly, and includes catalyst-supported particles having a hydrophobic coating, a polymer electrolyte, and hydrophilized carbon fibers having an average fiber length of 0.7 μm or more and 20 μm or less, the catalyst-supported particles include a support and a catalyst supported on the support, and when the content of the support is taken as 100 parts by mass, the content of the hydrophilized carbon fibers is 5 parts by mass or more and 30 parts by mass or less.
[0013] In the electrode catalyst layer, when the content of the carrier is taken as 100 parts by mass, the content of the polymer electrolyte may be 40 parts by mass or more and 100 parts by mass or less. In the electrode catalyst layer, the hydrophilized carbon fibers may have an average fiber diameter of 10 nm or more and 300 nm or less.
[0014] The membrane electrode assembly for solving the above problem includes a polymer electrolyte membrane and the above electrode catalyst layer, and the electrode catalyst layer is bonded to the polymer electrolyte membrane. A polymer fuel cell for solving the above problem includes the above membrane electrode assembly, a pair of gas diffusion layers that sandwich the membrane electrode assembly in the thickness direction of the membrane electrode assembly, and a pair of separators that sandwich the membrane electrode assembly and the pair of gas diffusion layers in the thickness direction of the membrane electrode assembly. Effect of the Invention
[0015] According to the present invention, it is possible to improve the power generation performance under both high humidification and low humidification operating conditions. [Brief description of the drawings]
[0016] [Figure 1] FIG. 2 is a cross-sectional view showing the structure of a membrane electrode assembly in one embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the structure of a first electrode catalyst layer in one embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing the structure of a catalyst-supporting particle contained in a first electrode catalyst layer in one embodiment. [Figure 4] 1 is an exploded perspective view showing a configuration of a polymer electrolyte fuel cell according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] An embodiment of an electrode catalyst layer, a membrane electrode assembly, and a polymer electrolyte fuel cell will be described with reference to Figures 1 to 4. The figures are appropriately exaggerated for ease of understanding. The configurations and materials of the electrode catalyst layer, the membrane electrode assembly, the polymer electrolyte fuel cell, and the manufacturing methods thereof of the present invention are not limited to the configurations and materials described below, but include all materials and configurations that are inferred to have similar functions.
[0018] [Membrane electrode assembly] As shown in FIG. 1, the membrane electrode assembly 10 includes a polymer electrolyte membrane 11, a cathode electrode catalyst layer 12C, and an anode electrode catalyst layer 12A.
[0019] The polymer electrolyte membrane 11 is a solid polymer electrolyte membrane. The polymer electrolyte membrane 11 is formed of, for example, a polymer material having proton conductivity. Examples of the polymer material having proton conductivity include fluororesins and hydrocarbon resins. Examples of the fluororesins include Nafion (manufactured by DuPont, registered trademark), Flemion (manufactured by AGC, registered trademark), and Gore-Select (manufactured by Gore, registered trademark). Examples of the hydrocarbon resins include engineering plastics and engineering plastics into which a sulfonic acid group has been introduced.
[0020] The cathode-side electrode catalyst layer 12C is an electrode catalyst layer constituting the air electrode, which is the cathode, and is bonded to one side of the polymer electrolyte membrane 11. The cathode-side electrode catalyst layer 12C is a layer for oxidizing protons transported through the polymer electrolyte membrane 11 with an oxidizing agent containing oxygen and receiving electrons from an external circuit. The anode-side electrode catalyst layer 12A is an electrode catalyst layer constituting the fuel electrode, which is the anode, and is bonded to the surface of the polymer electrolyte membrane 11 opposite to the surface to which the cathode-side electrode catalyst layer 12C is bonded. The anode-side electrode catalyst layer 12A is a layer for separating fuel gas into protons and electrons. In the following description, the cathode-side electrode catalyst layer 12C and the anode-side electrode catalyst layer 12A may be referred to as an electrode catalyst layer as a concept including the electrode catalyst layer.
[0021] [Electrode catalyst layer] Hereinafter, the first electrode catalyst layer and the second electrode catalyst layer as the electrode catalyst layer will be described. The cathode electrode catalyst layer 12C and the anode electrode catalyst layer 12A are both the first electrode catalyst layer. Alternatively, either one of the cathode electrode catalyst layer 12C and the anode electrode catalyst layer 12A is the first electrode catalyst layer, and the other is the second electrode catalyst layer. That is, at least one of the cathode electrode catalyst layer 12C and the anode electrode catalyst layer 12A is the first electrode catalyst layer. This provides an effect of improving the power generation performance under both high humidification and low humidification operating conditions. From the viewpoint of enhancing the above effect, when only one of the cathode electrode catalyst layer 12C and the anode electrode catalyst layer 12A is the first electrode catalyst layer, it is preferable that the cathode electrode catalyst layer 12C constituting the air electrode is the first electrode catalyst layer.
[0022] (1st electrode catalyst layer) 2, the first electrode catalyst layer 20 includes catalyst-supporting particles 21, a polymer electrolyte 22, and hydrophilized carbon fibers 23. The first electrode catalyst layer 20 may also include, as optional components, other known components contained in the electrode catalyst layer of a fuel cell.
[0023] <Catalyst-supported particles> As shown in FIG. 3, the catalyst-supporting particle 21 includes a catalyst 21a, a carrier 21b that supports the catalyst 21a, and a hydrophobic coating 21c that covers the catalyst 21a and the carrier 21b.
[0024] As the catalyst 21a, for example, a metal included in the platinum group, a metal other than the platinum group, or an alloy, oxide, double oxide, or carbide thereof can be used. Examples of metals included in the platinum group include platinum, palladium, ruthenium, iridium, rhodium, and osmium. Examples of metals other than the platinum group include gold, iron, lead, copper, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, and aluminum. Among these, platinum, gold, palladium, rhodium, ruthenium, and alloys thereof are preferred because of their high catalytic activity. The catalyst 21a constituting the catalyst-supported particle 21 may be only one of the above examples, or may be a combination of two or more of them.
[0025] The average particle diameter of the catalyst 21a is preferably, for example, 0.5 nm or more and 20 nm or less, and more preferably 1 nm or more and 5 nm or less. By setting the average particle diameter of the catalyst 21a to 0.5 nm or more, it is possible to suppress a decrease in stability. Furthermore, by setting the average particle diameter of the catalyst 21a to 20 nm or less, it is possible to suppress a decrease in activity. In this specification, the average particle diameter is defined as the arithmetic mean particle diameter obtained by particle size measurement.
[0026] The support 21b is made of a material that is conductive, is not corroded by the catalyst 21a, and is capable of supporting the catalyst 21a. Examples of the material constituting the support 21b include carbon materials such as carbon black, graphite, activated carbon, carbon nanotubes, carbon nanofibers, and fullerene. The support 21b constituting the catalyst-supported particle 21 may be one of the above examples, or a combination of two or more of them.
[0027] The shape of the support 21b is not particularly limited, and may be, for example, a particle shape or a fiber shape. From the viewpoint of smoothly transferring electrons generated on the surface of the catalyst 21a to the outside of the system, the support 21b is preferably in a shape capable of supporting the catalyst 21a on its outer surface.
[0028] The average particle diameter of the support 21b is, for example, preferably 10 nm or more and 1000 nm or less, more preferably 10 nm or more and 100 nm or less. By making the average particle diameter of the support 21b 10 nm or more, an electron conduction path is easily formed in the electrode catalyst layer. In addition, by making the average particle diameter of the support 21b 1000 nm or less, an increase in resistance due to an increase in the thickness of the first electrode catalyst layer 20 can be suppressed.
[0029] The hydrophobic coating 21c may be, for example, a coating made of a fluorine-based compound having at least one polar group. Examples of the polar group include a hydroxyl group, an alkoxy group, a carboxyl group, an ester group, an ether group, a carbonate group, and an amide group. The presence of the polar group allows the fluorine-based compound to be fixed to the outermost surface of the support 21b carrying the catalyst 21a. The portion of the fluorine-based compound other than the polar group is preferably a structure made of fluorine and carbon because of its high hydrophobicity and chemical stability. However, the hydrophobic coating 21c is not limited to such a structure as long as it has sufficient hydrophobicity and chemical stability.
[0030] The thickness of the hydrophobic coating 21c is preferably such that the reactive gas can sufficiently pass through it. For example, the thickness of the hydrophobic coating 21c is preferably 40 nm or less. In this case, the reactive gas can be sufficiently passed through, and the supply of the reactive gas to the active points can be prevented from being hindered.
[0031] In addition, the thickness of the hydrophobic coating 21c is preferably, for example, 2 nm or more. In this case, the catalyst-supporting particle 21 can be sufficiently hydrophobic, and the generated water generated in the electrode by the cell reaction can be sufficiently repelled. In addition, in this case, the accumulation of the generated water can be suppressed, and as a result, the supply of the reaction gas to the active site can be prevented from being hindered by the accumulated generated water.
[0032] <Polymer electrolyte> As the polymer electrolyte 22, a substance having proton conductivity is used. Examples of the substance having proton conductivity include fluorine-based polymer electrolytes and hydrocarbon-based polymer electrolytes. Examples of the fluorine-based polymer electrolyte include those having a tetrafluoroethylene skeleton, such as Nafion (registered trademark) manufactured by DuPont. Examples of the hydrocarbon-based polymer electrolyte include sulfonated polyether ketone, sulfonated polyether sulfone, sulfonated polysulfide, and sulfonated polyphenylene. The polymer electrolyte 22 constituting the first electrode catalyst layer 20 may be only one of the above examples, or may be a combination of two or more of them.
[0033] The content of the polymer electrolyte in the first electrode catalyst layer 20 is preferably, for example, 40 parts by mass or more and 100 parts by mass or less, when the content of the carrier 21b in the first electrode catalyst layer 20 is taken as 100 parts by mass. By making the content of the polymer electrolyte 40 parts by mass or more, it is possible to suppress a decrease in proton conductivity due to a defect in the proton conduction path. As a result, it becomes easy to ensure a balance between the proton conductivity and the electron conductivity in the first electrode catalyst layer 20. By making the content of the polymer electrolyte 100 parts by mass or less, it is possible to suitably expose the catalyst 21a of the catalyst-supporting particle 21. As a result, the catalytic activity in the first electrode catalyst layer 20 is improved.
[0034] <Hydrophilic carbon fiber> For example, hydrophilic carbon fibers manufactured to have hydrophilic properties, and hydrophilic carbon fibers obtained by subjecting non-hydrophilic carbon fibers to a treatment to impart hydrophilic properties can be used as the hydrophilic carbon fibers 23. Examples of treatments to impart hydrophilic properties include ozone or oxygen plasma treatment, electrolytic oxidation treatment, and mixed acid treatment.
[0035] The shape of the hydrophilized carbon fiber 23 is not particularly limited, and may be, for example, a hollow structure or a solid structure. Specific examples of the hydrophilized carbon fiber 23 include VGCF (Vapor Grown Carbon Fiber) and CNT (Carbon Nano Tube). The hydrophilized carbon fiber 23 constituting the first electrode catalyst layer 20 may be only one of the above examples, or may be a combination of two or more types.
[0036] The average fiber length of the hydrophilized carbon fibers 23 is 0.7 μm or more and 20 μm or less. By setting the average fiber length of the hydrophilized carbon fibers 23 within the above range, it is possible to improve the moisture retention of the first electrode catalyst layer 20 by using the hydrophilized carbon fibers 23, while improving the power generation performance of the fuel cell.
[0037] In more detail, the main effects obtained by including the hydrophilized carbon fibers 23 in the first electrode catalyst layer 20 are moisture retention in the first electrode catalyst layer 20, establishment of an electron conduction path in the first electrode catalyst layer 20, and structural reinforcement of the first electrode catalyst layer 20. By setting the average fiber length of the hydrophilized carbon fibers 23 to 0.7 μm or more, a network between the hydrophilized carbon fibers 23 is easily formed. This allows the establishment of an electron conduction path in the first electrode catalyst layer 20 and the structural reinforcement of the first electrode catalyst layer 20 to be sufficiently performed, resulting in improved power generation performance of the fuel cell. By setting the average fiber length of the hydrophilized carbon fibers 23 to 20 μm or less, the dispersibility of the hydrophilized carbon fibers 23 can be improved when the first electrode catalyst layer 20 is formed using a catalyst ink described later.
[0038] In addition, in a fuel cell, the amount of water generated in the electrode catalyst layer as a result of the cell reaction is proportional to the amount of chemical reaction. Therefore, when power is generated at a high current density, the amount of water generated increases. If this water is not sufficiently drained out of the electrode catalyst layer, the water remaining in the electrode catalyst layer may block the gas diffusion path. In this case, flooding occurs, which is a phenomenon in which the reactive gas cannot reach the active site and the power generation performance is significantly reduced.
[0039] By setting the average fiber length of the hydrophilized carbon fibers 23 to 20 μm or less, sufficient voids can be secured within the first electrode catalyst layer 20, improving the drainage performance of the first electrode catalyst layer 20. As a result, flooding is less likely to occur even when power is generated at a high current density, improving the power generation performance of the fuel cell.
[0040] The average fiber diameter of the hydrophilized carbon fibers 23 is preferably, for example, 10 nm or more and 300 nm or less. In this case, since voids of an appropriate size can be formed in the first electrode catalyst layer 20, the gas diffusion property in the first electrode catalyst layer 20 is improved.
[0041] The content of the hydrophilized carbon fiber 23 in the first electrode catalyst layer 20 is 5 parts by mass or more and 30 parts by mass or less, when the content of the support 21b in the first electrode catalyst layer 20 is taken as 100 parts by mass. In addition, the content of the hydrophilized carbon fiber 23 is preferably 5 parts by mass or more and 20 parts by mass or less.
[0042] By setting the content of the hydrophilized carbon fibers 23 to 5 parts by mass or more, a network between the hydrophilized carbon fibers 23 is easily formed. This allows the construction of an electron conduction path in the electrode catalyst layer and the structural reinforcement of the electrode catalyst layer to be sufficiently achieved. As a result, the power generation performance of the fuel cell is improved. By setting the content of the hydrophilized carbon fibers 23 to 30 parts by mass or less, an increase in resistance due to an increase in the thickness of the first electrode catalyst layer 20 can be suppressed.
[0043] (Second electrode catalyst layer) The second electrode catalyst layer may be a known electrode catalyst layer applied to a membrane electrode assembly. For example, the second electrode catalyst layer may be an electrode catalyst layer that is different from the first electrode catalyst layer 20 in that it uses catalyst-supporting particles 21 that do not have a hydrophobic coating 21c and does not include hydrophilized carbon fibers 23, but has the same configuration as the first electrode catalyst layer 20 in other respects.
[0044] With regard to the above-mentioned materials used as components of the first electrode catalyst layer and the second electrode catalyst layer, the material used for the cathode side electrode catalyst layer 12C may be the same as or at least partially different from the material used for the anode side electrode catalyst layer 12A.
[0045] [Polymer electrolyte fuel cell] Next, a configuration of a polymer electrolyte fuel cell including the membrane electrode assembly 10 will be described. A single-cell polymer electrolyte fuel cell will be described below as an example of a polymer electrolyte fuel cell. The polymer electrolyte fuel cell is not limited to a single-cell configuration, and may include a plurality of single cells, and may be configured such that the plurality of single cells are stacked.
[0046] As shown in FIG. 4, a polymer electrolyte fuel cell 30 includes a membrane electrode assembly 10, a pair of gas diffusion layers 31a, 31b, and a pair of separators 32a, 32b. The gas diffusion layers 31a and 31b are layers for uniformly diffusing the reaction gas. The gas diffusion layer 31a is disposed so as to face the cathode side electrode catalyst layer 12C of the membrane electrode assembly 10. The gas diffusion layer 31b is disposed so as to face the anode side electrode catalyst layer 12A of the membrane electrode assembly 10. The pair of gas diffusion layers 31a and 31b sandwich the membrane electrode assembly 10 in the thickness direction of the membrane electrode assembly 10. The cathode side electrode catalyst layer 12C and the gas diffusion layer 31a form an air electrode, which is a cathode. The anode side electrode catalyst layer 12A and the gas diffusion layer 31b form a fuel electrode, which is an anode.
[0047] The gas diffusion layers 31a and 31b are made of a material having electronic conductivity and gas diffusion properties. For example, a porous carbon material can be used as the material for the gas diffusion layers 31a and 31b. For example, the porous carbon material can be carbon cloth, carbon paper, or nonwoven fabric.
[0048] The separators 32a and 32b are members that serve to extract electrons to an external circuit, and are disposed on the outer side of the gas diffusion layer 31b. The pair of separators 32a and 32b sandwich the membrane electrode assembly 10 and the pair of gas diffusion layers 31a and 31b in the thickness direction of the membrane electrode assembly 10.
[0049] The separators 32a and 32b have gas flow paths 33a and 33b and cooling water flow paths 34a and 34b. The gas flow paths 33a and 33b are flow paths for flowing reactive gases and are formed on the surfaces of the separators 32a and 32b facing the gas diffusion layers 31a and 31b. The cooling water flow paths 34a and 34b are flow paths for flowing cooling water and are formed on the surfaces of the separators 32a and 32b opposite to the surfaces facing the gas diffusion layers 31a and 31b.
[0050] The separators 32a and 32b are made of a material that is electrically conductive and gas impermeable. Examples of the material that constitutes the separators 32a and 32b include carbon materials and metal materials. In addition, it is preferable that the material that constitutes the separators 32a and 32b has a certain degree of strength and good moldability.
[0051] An oxidant gas serving as a reactant gas is supplied to the gas flow passage 33a of the separator 32a facing the gas diffusion layer 31a constituting the air electrode. The oxidant gas is, for example, air or oxygen gas. A fuel gas serving as a reactant gas is supplied to the gas flow passage 33b of the separator 32b facing the gas diffusion layer 31b constituting the fuel electrode. The fuel gas is, for example, hydrogen gas.
[0052] In the polymer electrolyte fuel cell 30, a fuel gas containing hydrogen is supplied to the fuel electrode, and an oxidant gas containing oxygen is supplied to the air electrode, whereby electrode reactions occur at the fuel electrode and the air electrode, as shown in the following formulas 1 and 2, to generate electricity. The polymer electrolyte fuel cell is used in combination with auxiliary devices such as a gas supply device and a cooling device.
[0053] Fuel electrode: H2→2H + +2e - ...(Formula 1) Air electrode: 1 / 2O2+2H + +2e - →H2O...(Formula 2) [Method of manufacturing membrane electrode assembly] A method for producing the membrane electrode assembly 10 will now be described.
[0054] The method for producing the membrane electrode assembly 10 includes a preparation step of preparing a catalyst ink, and a formation step of forming an electrode catalyst layer using the catalyst ink. (Preparation process) In the preparation step, the components constituting the electrode catalyst layer are mixed using a dispersion medium to prepare a catalyst ink.
[0055] The dispersion medium is not particularly limited as long as it can disperse each component constituting the electrode catalyst layer. Examples of the dispersion medium include water, alcohol, ketones, and mixtures thereof. Specifically, water, alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, and tert-butyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, methyl amyl ketone, pentanone, heptanone, cyclohexanone, methyl cyclohexanone, acetonylacetone, diethyl ketone, dipropyl ketone, and diisobutyl ketone can be appropriately used.
[0056] The catalyst ink may also contain a dispersant for dispersing the components constituting the electrode catalyst layer. Examples of the dispersant include anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants.
[0057] Examples of anionic surfactants include alkyl ether carboxylates, ether carboxylates, alkanoyl sarcosines, alkanoyl glutamates, acyl glutamates, oleic acid·N-methyl taurine, potassium oleate·diethanolamine salts, alkyl ether sulfate·triethanolamine salts, polyoxyethylene alkyl ether sulfate·triethanolamine salts, amine salts of specially modified polyether ester acids, amine salts of higher fatty acid derivatives, amine salts of specially modified polyester acids, amine salts of high molecular weight polyether ester acids, amine salts of specially modified phosphate esters, amidoamine salts of high molecular weight polyester acids, amidoamine salts of special fatty acid derivatives, alkylamine salts of higher fatty acids, amidoamine salts of high molecular weight polycarboxylic acids, carboxylic acid surfactants such as sodium laurate, sodium stearate, and sodium oleate, dialkyl sulfosuccinates, dialkyl sulfosuccinates, 1,Sulfonic acid surfactants such as 2-bis(alkoxycarbonyl)-1-ethanesulfonate, alkyl sulfonate, alkyl sulfonate, paraffin sulfonate, α-olefin sulfonate, linear alkylbenzene sulfonate, alkylbenzene sulfonate, polynaphthylmethanesulfonate, polynaphthylmethanesulfonate, naphthalenesulfonate-formaldehyde condensate, alkylnaphthalenesulfonate, alkanoylmethyl tauride, sodium lauryl sulfate, sodium cetyl sulfate, sodium stearyl sulfate, sodium oleyl sulfate, lauryl ether sulfate, sodium alkylbenzenesulfonate, oil-soluble alkylbenzenesulfonate, and α-olefinsulfonate, alkyl sulfate, alkyl sulfate, alkyl ether sulfate, polyoxyethylene sulfonate ... Examples of the phosphate ester surfactants include ethylene alkyl ether sulfate, alkyl polyethoxy sulfate, polyglycol ether sulfate, alkyl polyoxyethylene sulfate, sulfated oil, and highly sulfated oil; (mono- or di-) alkyl phosphate salt, (mono- or di-) alkyl phosphate salt, (mono- or di-) alkyl phosphate ester salt, alkyl polyoxyethylene phosphate salt, alkyl ether phosphate, alkyl polyethoxy phosphate salt, polyoxyethylene alkyl ether, alkyl phenyl polyoxyethylene phosphate salt, alkyl phenyl ether phosphate, alkyl phenyl polyethoxy phosphate salt, polyoxyethylene alkyl phenyl ether phosphate, higher alcohol phosphate monoester disodium salt, higher alcohol phosphate diester disodium salt, and zinc dialkyl dithiophosphate.
[0058] Examples of cationic surfactants include benzyldimethyl{2-[2-(P-1,1,3,3-tetramethylbutylphenoxy)ethoxy]ethyl}ammonium chloride, octadecylamine acetate, tetradecylamine acetate, octadecyltrimethylammonium chloride, beef tallow trimethylammonium chloride, dodecyltrimethylammonium chloride, coconut trimethylammonium chloride, hexadecyltrimethylammonium chloride, behenyltrimethylammonium chloride, coconut dimethylbenzyl ammonium chloride, tetradecyldimethylbenzyl ammonium chloride, and tetradecyldimethylbenzyl ammonium chloride. Examples of suitable quaternary ammonium iodides include 1-hydroxyethyl-2-beef tallow imidazoline quaternary salt, 2-heptadecenyl-hydroxyethyl imidazoline, stearamidoethyl diethylamine acetate, stearamidoethyl diethylamine hydrochloride, triethanolamine monostearate formate, alkyl pyridinium salts, higher alkylamine ethylene oxide adducts, polyacrylamide amine salts, modified polyacrylamide amine salts, and perfluoroalkyl quaternary ammonium iodides.
[0059] Examples of amphoteric surfactants include dimethyl coconut betaine, dimethyl lauryl betaine, sodium lauryl aminoethyl glycine, sodium lauryl aminopropionate, stearyl dimethyl betaine, lauryl dihydroxyethyl betaine, amido betaine, imidazolinium betaine, lecithin, sodium 3-[ω-fluoroalkanoyl-N-ethylamino]-1-propanesulfonate, and N-[3-(perfluorooctanesulfonamido)propyl]-N,N-dimethyl-N-carboxymethylene ammonium betaine.
[0060] Examples of nonionic surfactants include coconut fatty acid diethanolamide (1:2 type), coconut fatty acid diethanolamide (1:1 type), cow fatty acid diethanolamide (1:2 type), cow fatty acid diethanolamide (1:1 type), oleic acid diethanolamide (1:1 type), hydroxyethyl laurylamine, polyethylene glycol laurylamine, polyethylene glycol coconut amine, polyethylene glycol stearylamine, polyethylene glycol tallow amine, polyethylene glycol tallow propylene diamine, polyethylene glycol dioleylamine, dimethyl laurylamine oxide, dimethyl stearylamine oxide, dihydroxyethyl laurylamine oxide, perfluoroalkylamine oxide, polyvinylpyrrolidone, higher alcohol ethylene oxide adducts, alkylphenol ethylene oxide adducts, fatty acid ethylene oxide adducts, polypropylene glycol ethylene oxide adducts, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol, fatty acid esters of sorbitan, and fatty acid esters of sugar.
[0061] Among the above surfactants, sulfonic acid type surfactants such as alkylbenzene sulfonic acid, oil-soluble alkylbenzene sulfonic acid, α-olefin sulfonic acid, sodium alkylbenzene sulfonate, oil-soluble alkylbenzene sulfonate, and α-olefin sulfonate can be suitably used as dispersants because they have an excellent carbon dispersion effect and are unlikely to cause a change in catalyst performance due to residual dispersant.
[0062] The dispersion method in the preparation step is not particularly limited as long as it can disperse each component contained in the catalyst ink, and any known dispersion method can be used. Examples of known dispersion methods include methods using a planetary ball mill, a bead mill, or an ultrasonic homogenizer. The blending ratio of each component and the dispersion medium in the catalyst ink can be appropriately selected depending on the coatability and the required power generation performance.
[0063] (Formation process) In the forming step, the catalyst ink obtained in the preparation step is applied to a substrate, and then a drying process is performed to volatilize the dispersion medium, thereby forming a coating-like electrode catalyst layer. The substrate may be the polymer electrolyte membrane 11, a transfer substrate, or the gas diffusion layers 31a and 31b.
[0064] The application method for applying the catalyst ink to the substrate is not particularly limited, and any known application method that is applied when applying a slurry mixture to a substrate with a uniform film thickness can be used. Examples of known application methods include die coating, bar coating, spray coating, dipping, and screen printing. Among these, it is preferable to use the die coating method, since the viscosity range of the catalyst ink that can be applied is relatively wide, and the ink can be applied with high film thickness uniformity.
[0065] The drying method used in the drying treatment is not particularly limited as long as it is a method that can volatilize the dispersion medium, and known drying methods such as a method using an oven, a hot plate, far infrared rays, etc. In addition, the drying temperature and drying time in the drying treatment can be appropriately selected depending on the materials used for the electrode catalyst layer and the substrate.
[0066] When a transfer substrate is used as the substrate, a process is performed to transfer the electrode catalyst layer formed on the transfer substrate from the transfer substrate to the polymer electrolyte membrane 11. As a transfer method at that time, for example, a transfer method using thermocompression bonding can be used.
[0067] The transfer substrate is not particularly limited as long as it can release the formed electrode catalyst layer and transfer it to the polymer electrolyte membrane. For example, a fluororesin film can be used as the transfer substrate. The fluororesin film has excellent transferability. Examples of the fluororesin constituting the fluororesin film include ethylene tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroperfluoroalkylvinylether copolymer (PFA), and polytetrafluoroethylene (PTFE).
[0068] When the polymer electrolyte membrane 11 or the transfer substrate is used as the transfer substrate, a membrane electrode assembly 10 is obtained by providing electrode catalyst layers on both sides of the polymer electrolyte membrane 11. Then, a solid polymer fuel cell 30 is obtained by laminating the obtained membrane electrode assembly 10, gas diffusion layers 31a and 31b, and separators 32a and 32b.
[0069] When the gas diffusion layers 31a and 31b are used as the transfer substrate, the polymer electrolyte membrane 11 and the gas diffusion layers 31a and 31b on which the electrode catalyst layers are formed are laminated to obtain a membrane electrode assembly 10 having the gas diffusion layers 31a and 31b. Then, the separators 32a and 32b are laminated on the obtained membrane electrode assembly 10 to obtain a polymer electrolyte fuel cell 30.
[0070] The manufacturing method of the electrode catalyst layer when manufacturing the cathode side electrode catalyst layer 12C and the manufacturing method of the electrode catalyst layer when manufacturing the anode side electrode catalyst layer 12A may be the same or different. EXAMPLES
[0071] Next, the above embodiment will be described in more detail with reference to examples and comparative examples. Note that the present invention is not limited to the configurations described in the examples section. [Example 1] A catalyst ink was prepared by carrying out a dispersion treatment on a mixture of catalyst-supported particles, a polymer electrolyte, carbon fiber, and a dispersion medium. The amount of polymer electrolyte was 70 parts by mass relative to the amount of carrier contained in the catalyst-supported particles, i.e., 100 parts by mass of catalyst-supported particles in terms of carrier. The amount of carbon fiber was 20 parts by mass relative to 100 parts by mass of catalyst-supported particles in terms of carrier. The amount of dispersion medium was an amount such that the solid content concentration of the catalyst ink was 10% by mass. The dispersion treatment was carried out for 60 minutes at a rotation speed of 600 rpm using zirconia balls with a diameter of 3 mm and a planetary ball mill. Details of each component used in the catalyst ink are as follows.
[0072] Catalyst-supported particles: Platinum-supported carbon catalyst with a hydrophobic coating formed from a fluorine-based compound (support density 50 mass%, hydrophobic coating thickness 25 nm) Polymer electrolyte: Fluorine-based polymer electrolyte (Nafion (registered trademark) dispersion liquid manufactured by Wako Pure Chemical Industries, Ltd.) Carbon fiber: Carbon fiber (average fiber length 6 μm, average fiber diameter 150 nm) that was hydrophilized by oxygen plasma treatment on non-hydrophilized carbon fiber (VGCF-H (registered trademark) manufactured by Showa Denko K.K.) Dispersion medium: A mixture of water and 1-propanol in a mass ratio of 1:1 Next, the prepared catalyst ink was applied to one side of a polymer electrolyte membrane (Nafion (registered trademark) 211 manufactured by Dupont) using a die coater to form a rectangular coating film with a length of 50 mm and a width of 50 mm. The amount of the catalyst ink applied was 0.3 mg / cm2 for platinum loading. 2 Then, a drying process was carried out using an oven at 80° C. to volatilize the dispersion medium contained in the coating film, thereby forming a cathode-side electrode catalyst layer.
[0073] Next, the prepared catalyst ink was applied to the surface of the polymer electrolyte membrane opposite to the surface on which the cathode electrode catalyst layer was formed, to form a rectangular coating film measuring 50 mm in length and 50 mm in width. The amount of catalyst ink applied was such that the platinum loading was 0.1 mg / cm. 2 Then, a drying treatment was carried out using an oven at 80° C. to volatilize the dispersion medium contained in the coating film, thereby forming an anode-side electrode catalyst layer, and thus a membrane / electrode assembly of Example 1 was obtained.
[0074] [Comparative Example 1] Except for changing the type of catalyst-supporting particles, a membrane / electrode assembly of Comparative Example 1 was obtained in the same manner as in Example 1. Details of the catalyst-supporting particles used in Comparative Example 1 are as follows.
[0075] Catalyst-supported particles: Platinum-supported carbon catalyst without a hydrophobic coating (support density 50% by mass) [Comparative Example 2] Except for changing the type of carbon fiber, a membrane / electrode assembly of Comparative Example 2 was obtained in the same manner as in Example 1. Details of the carbon fiber used in Comparative Example 2 are as follows.
[0076] Carbon fiber: Non-hydrophilized carbon fiber (VGCF-H (registered trademark) manufactured by Showa Denko K.K., average fiber length 6 μm, average fiber diameter 150 nm) [Comparative Example 3] Except for changing the type of catalyst-supporting particles and the type of carbon fiber, a membrane electrode assembly of Comparative Example 3 was obtained in the same manner as in Example 1. Details of the catalyst-supporting particles and carbon fiber used in Comparative Example 3 are as follows.
[0077] Catalyst-supported particles: Platinum-supported carbon catalyst without a hydrophobic coating (support density 50% by mass) Carbon fiber: Non-hydrophilized carbon fiber (VGCF-H (registered trademark) manufactured by Showa Denko K.K., average fiber length 6 μm, average fiber diameter 150 nm) [Comparative Example 4] A membrane / electrode assembly of Comparative Example 4 was obtained in the same manner as in Example 1, except that the amount of carbon fiber was 70 parts by mass per 100 parts by mass of the catalyst-supporting particles calculated as the carrier.
[0078] [Comparative Example 5] A membrane / electrode assembly of Comparative Example 5 was obtained in the same manner as in Example 1, except that the amount of carbon fiber was 2 parts by mass per 100 parts by mass of the catalyst-supported particles calculated as the carrier.
[0079] [Evaluation of power generation performance] For each of the membrane electrode assemblies of Example 1 and Comparative Examples 1 to 5, a sample was prepared by bonding carbon paper, which is a gas diffusion layer, so as to sandwich the membrane electrode assembly. Each sample was placed in a power generation evaluation cell, and current and voltage measurements were performed using a fuel cell measurement device. The cell temperature during the measurements was set to 80°C. The following high humidity conditions and low humidity conditions were adopted as operating conditions. Hydrogen was used as the fuel gas, and air was used as the oxidant gas. At this time, hydrogen was flowed at a flow rate such that the hydrogen utilization rate was 80%, and air was flowed at a flow rate such that the oxygen utilization rate was 40%. The back pressure was set to 50 kPa.
[0080] (Operating conditions) High humidity conditions: Relative humidity anode 90%RH, cathode 80%RH Low humidity conditions: Relative humidity anode 90%RH, cathode 30%RH The measured power generation performance of each sample is shown in the power generation performance column of Table 1. In Table 1, the power generation performance is shown at a current density of 2.0 A / cm 2 If the voltage is 0.65V or higher, it is indicated with an "O", and if the voltage is less than 0.65V, it is indicated with an "X".
[0081] [Table 1] As shown in Table 1, when Example 1 was used, good power generation performance was shown under both high and low humidification operating conditions. In addition, since the power generation performance under high humidification was evaluated as "good", it is considered that flooding did not occur under high humidification conditions when Example 1 was used, and the generated water was sufficiently drained.
[0082] On the other hand, when Comparative Example 1, which employed catalyst-supported particles without a hydrophobic coating, was used, the power generation performance under high humidification conditions was reduced. When Comparative Example 2, which employed carbon fiber that was not hydrophilized, was used, the power generation performance under low humidification conditions was reduced. When Comparative Example 3, which employed catalyst-supported particles without a hydrophobic coating and carbon fiber that was not hydrophilized, was used, the power generation performance under both high and low humidification conditions was reduced.
[0083] The results of Example 1 and Comparative Examples 1 to 3 show that the use of a combination of catalyst-supported particles with a hydrophobic coating and hydrophilized carbon fibers can improve the power generation performance under both high and low humidification operating conditions. The mechanism by which this effect is obtained is presumed to be as follows. In Example 1, the catalyst ink forming the electrode catalyst layer contains catalyst-supported particles with a hydrophobic coating, which is a hydrophobic material, and hydrophilized carbon fibers, which is a hydrophilic material. As a result, when the applied catalyst ink is dried to form the electrode catalyst layer, the configuration of the shape and distribution of the voids formed in the electrode catalyst layer becomes suitable for discharging liquid water outside the layer while leaving gaseous water in the layer during power generation. As a result, the power generation performance is improved under both high and low humidification operating conditions.
[0084] In addition, when Comparative Example 4 and Comparative Example 5, in which the content of hydrophilized carbon fiber was outside the range of 5 parts by mass or more and 30 parts by mass or less, were used, the power generation performance under both high and low humidification conditions was reduced. The results of Comparative Example 4 and Comparative Example 5 showed that the effect of improving the power generation performance under high and low humidification conditions obtained by Example 1 cannot be obtained by simply combining and using catalyst-supported particles with a hydrophobic coating and hydrophilized carbon fiber. In order to obtain the above effect, it was shown that in addition to using catalyst-supported particles with a hydrophobic coating and hydrophilized carbon fiber, the content of hydrophilized carbon fiber needs to be set within a specific range. [Explanation of symbols]
[0085] 10...Membrane electrode assembly 11...Polymer electrolyte membrane 12C…Cathode side electrode catalyst layer 12A: Anode side electrode catalyst layer 20...First electrode catalyst layer 21...Catalyst-supporting particles 21a...Catalyst 21b...Carrier 21c…Hydrophobic coating 22...polymer electrolyte 23...Hydrophilic carbon fiber 30...Polymer fuel cell 31a, 31b...gas diffusion layer 32a, 32b…Separator 33a, 33b...gas flow path 34a, 34b...Cooling water flow path
Claims
1. An electrode catalyst layer bonded to a polymer electrolyte membrane in a membrane electrode assembly, The present invention includes a catalyst-supporting particle having a hydrophobic coating, a polymer electrolyte, and a hydrophilized carbon fiber having an average fiber length of 0.7 μm or more and 20 μm or less, The catalyst-supporting particle includes a support and a catalyst supported on the support, An electrode catalyst layer, characterized in that the content of the hydrophilized carbon fiber is 5 parts by mass or more and 30 parts by mass or less when the content of the support is taken as 100 parts by mass.
2. 2 . The electrode catalyst layer according to claim 1 , wherein the content of the polymer electrolyte is 40 parts by mass or more and 100 parts by mass or less when the content of the carrier is taken as 100 parts by mass.
3. 3. The electrode catalyst layer according to claim 1, wherein the hydrophilized carbon fibers have an average fiber diameter of 10 nm or more and 300 nm or less.
4. A polymer electrolyte membrane; and the electrode catalyst layer according to any one of claims 1 to 3, A membrane electrode assembly in which the electrode catalyst layer is bonded to the polymer electrolyte membrane.
5. The membrane electrode assembly according to claim 4 ; a pair of gas diffusion layers sandwiching the membrane electrode assembly in a thickness direction of the membrane electrode assembly; a pair of separators sandwiching the membrane electrode assembly and the pair of gas diffusion layers in a thickness direction of the membrane electrode assembly;
Citation Information
Patent Citations
Solid polymer fuel cell and method of manufacturing same
JP2004031325A
Electrode catalyst layer for fuel cell and fuel cell using it
JP2006216385A
Electrode, membrane electrode assembly, electrochemical cell, stack, fuel cell, vehicle, and flying object
JP2019169315A
Membrane-electrode assembly for fuel cell, and solid polymer electrolyte fuel cell
JP2020061248A
Membrane-electrode assembly for fuel cell, and solid polymer electrolyte fuel cell
JP2020061249A